Five cases of bacteraemia due to Gordonia species - Brust, James C M; Whittier, Susan; Scully, Brian E; McGregor, Carlton C; Yin, Michael T (Journal of medical microbiology, 2009)
Gordonia species are aerobic Gram-positive bacilli and a rare cause of human disease. To our knowledge, there are only two cases of human infection with Gordonia sputi reported in the literature. We report five cases of bacteraemia due to Gordonia species at our institution since 2005, including four caused by G. sputi. Three of these cases were likely related to chronic indwelling central venous catheters.